Self Management Support for Cardiac Catheterization Patients - Selvia Feri Marselina; Erwin Erwin; Musfardi Rustam (Journal of Education Technology Information Social Sciences and Health, 2024)
Introduction: Cardiac catheterization is an invasive procedure to detect blockages in the coronary arteries. Risk factors can be prevented with self-management support. Self-Management-Support care and support is provided by emphasizing the importance of the patient's central role in managing their own health. Method: This research uses a descriptive design. The research sample was 30 respondents taken based on inclusion criteria using accidental sampling technique. The measuring instrument used is a questionnaire sheet. The analysis used is univariate analysis which aims to describe the frequency distribution to find out the description of Self Management and Support in Cardiac Catheterization Patients. Results: The assessment results for all respondents are in the medium category, namely with a total of 20 respondents (66.7%), Adsive is in the good category, namely with the number 15 respondents (50%), Agree in the good category, namely with a total of 25 respondents (83.3%), Assist in the medium category, namely with a total of 23 respondents (76.7%), and Arrange in the medium category, namely with a total of 15 respondents (50%) . This research suggests that health workers continue to provide self-management support to cardiac catheterization patients to improve patient health.